2021
DOI: 10.1021/acsnano.0c03595
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Coherent Phonon Transport in Ultralow Thermal Conductivity Two-Dimensional Ruddlesden–Popper Phase Perovskites

Abstract: An emerging class of methylammonium lead iodide (MAPbI 3 )-based Ruddlesden−Popper (RP) phase perovskites, BA 2 MA n−1 Pb n I 3n+1 (n = 1−7), exhibit enhanced stability to environmental conditions relative to MAPbI 3 , yet still degrade at elevated temperatures. We experimentally determine the thermal conductivities of these layered RP phases for n = 1−6, where n defines the number of repeated perovskite octahedra per layer. We measure thermal conductivities of 0.37 ± 0.13/0.12, 0.17 ± 0.08/0.07, 0.21 ± 0.05/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 59 publications
3
45
0
Order By: Relevance
“…[31] Concerning vibrations across the bilayer structure, cross-plane coherent acoustic phonons have been also reported. [34,35] The organic layer determines the distortions of the inorganic layer, and thereby influences the optical and vibrational properties of the 2DLPs. [8,28,29,36] Vibrational bands related to the organic moieties that appear at higher frequencies can also impact the band edge emission process.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Concerning vibrations across the bilayer structure, cross-plane coherent acoustic phonons have been also reported. [34,35] The organic layer determines the distortions of the inorganic layer, and thereby influences the optical and vibrational properties of the 2DLPs. [8,28,29,36] Vibrational bands related to the organic moieties that appear at higher frequencies can also impact the band edge emission process.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, this material exhibited anisotropic thermal conductivity, which is not unexpected considering the fact that it is all-inorganic, while it has been shown that the orientational effects of bulky organic spacer cations significantly affect out-of-plane thermal conductivity and that complex interactions involving inorganic components and organic spacers can lead to comparable phonon group velocities in both directions for an organic–inorganic 2D MHPs such as BA 2 PbI 4 . In addition, it was shown that for quasi-2D BA 2 MA n ‑1 Pb n I 3 n +1 single crystals, very low κ values (below 0.1 W m –1 K –1 ) could be obtained for RP perovskite single crystals with n = 3–6 . While the thermal conductivities of these films were higher than in single crystals due to random orientation of the polycrystalline grains, higher n value quasi-2D single crystals are particularly promising due to reduced group velocities of coherent phonons as a consequence of band flattening in the phonon dispersion leading to reduced thermal conductivity .…”
Section: Thermoelectric Properties Of Metal Halide Perovskitesmentioning
confidence: 70%
“…As an example, Giri et al reported thermal conductivities of different 2D MHPs through experiments and simulations, where iso-BA 2 PbI 4 exhibited a theoretical thermal conductivity as low as 0.1 W m –1 K –1 . Thermal conductivities which are significantly lower than that of 3D perovskites have been reported to date for several 2D and quasi-2D MHPs, ,,, but it should be noted that there could be significant differences between the samples with same composition but different film preparation methods, and between thin films and single crystals.…”
Section: Thermoelectric Properties Of Metal Halide Perovskitesmentioning
confidence: 80%
See 1 more Smart Citation
“…Importantly, the VPVP provides direct information on the local temperature, which opens a possibility of spatiotemporal thermal imaging at both near-equilibrium and far-fromequilibrium conditions, the latter made possible by direct impulsive thermal stimulation of the targeted material with higher-energy MIR pulses than used in this work. We anticipate that the demonstrated VPVP technique can be employed for investigating thermal transport in disordered materials such as organic or polymeric semiconducting films, 49 metal-organic frameworks, 50 covalent organic frameworks, 51 biological materials, 52 and low-dimensional halide perovskites, [53][54][55][56] some of which may not be amenable to high-vacuum deposition of metallic transducers atop.…”
Section: Discussionmentioning
confidence: 99%